Family health program user: knowledge and satisfaction about user embracement - doi: 10.5020/18061230.2012.s96 - Saulo Lacerda Borges de Sá; Raquel Rodrigues Mattos; Vitor Lima Pinheiro; Lucianna Leite Pequeno; Maria Albertina Rocha Diógenes (Universidade de Fortaleza, 2012)
Objective: To assess the knowledge and satisfaction of users of a Basic Health Unit about the strategy of embracement. Methods: Descriptive study with qualitative approach, carried out in a Basic Health Unit, Fortaleza, Brazil, where practical activities of the Education Program of Work for Health of the University of Fortaleza were performed. Fifty eight service users were involved, following inclusion criteria: being present during the data collection, age over 18, regardless of sex, and voluntary participation. Data collection occurred in December 2009, through semi-structured interview. The data associated with the identification of users were processed in Microsoft Office Excel 2007, being organized statistically in table. Data related to qualitative aspects were analyzed according to the technique of content analysis. Results: 56 (97%) were women, with ages ranging between 21 and 40 years, 34 (59%) were married and 53 (91%) are literate. On family income, 55 (95%) received less than two minimum salaries per month. In order to facilitate understanding the speech of users, these were evaluated from the perspective of two categories: knowledge about embracement and satisfaction with embracement. Conclusion: Users have a limited view of the significance and magnitude of the embracement to provide the care. Although satisfied with the service, respondents report as negative aspects: the shortage of professionals, the professional relationship with user impaired due to constant delays of the professional, and the dehumanization of care.